2016
DOI: 10.1080/08927022.2016.1172704
|View full text |Cite
|
Sign up to set email alerts
|

On the oblique collision of gaseous molecules with graphene nanosheets

Abstract: In this paper, normal and tangential coefficients of restitution for gaseous molecules colliding with layerwise (single and few layers) graphene nanosheets were calculated using non-equilibrium molecular dynamics method. The normal and tangential coefficients of restitution depend on impact angle, velocity and landing position of projectiles. These parameters were evaluated computationally by implementation of several operations. Some differences were observed between proposed problem and macro-scale nature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This is the main idea for gas storage. Bombardment of graphene sheets by several gaseous molecules [15] and especially oxygen [4] was studied to control defect generation [16]. Furthermore, some recent works focused on mass detection of metallic nanoparticles [17].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This is the main idea for gas storage. Bombardment of graphene sheets by several gaseous molecules [15] and especially oxygen [4] was studied to control defect generation [16]. Furthermore, some recent works focused on mass detection of metallic nanoparticles [17].…”
Section: Theorymentioning
confidence: 99%
“…Figure15. Ruptured structure of a two-layer graphene sheet before being impacted by a relatively rigid nanocluster, after passing the rst layer, after passing the second layer, and after getting far away from the graphene sheet.…”
mentioning
confidence: 99%
“…Comparisons demonstrated that graphenebased plate has considerably more resistance against the projectile than metal micro plates. The withstanding ratio of graphene with respect to the steel, gold, and aluminum plates with five layers of atoms is reported between 0.5 and 6.5 for single-to twenty-layer graphene sheets [19]. The middle and the rightmost schematics in Fig.…”
Section: Withstanding the Impact Of Nanoparticles By Mlgssmentioning
confidence: 98%
“…Using molecular dynamics (MD) method, Abdol et al [32] built a three-dimensional graphene networks via silicon ion beam irradiation. In a series reports by Sadeghzadeh [34,[39][40][41][42] , the graphene sheets were impacted with various kinds of high speed projectiles, and the effects of several parameters on the rupture form and penetration-resistance efficiency of the graphene ribbons were evaluated systematically. In the experiments by Eller et al [43] , few layered graphene were bombarded with golden nanoparticles, and the ejection of ions from graphene were characterized.…”
Section: Introductionmentioning
confidence: 99%